Salivary cortisol levels and anxiety in melanoma patients undergoing sentinel lymph node excision under local anesthesia versus general anesthesia: a prospective study - Jansen, Philipp; Stoffels, Ingo; Müseler, Anne-Christine; Petri, Maximilian; Brinker, Titus Josef; Schedlowski, Manfred; Schadendorf, Dirk; Engler, Harald Raimund; Klode, Joachim (World journal of surgical oncology, 2020)
Sentinel lymph node excision (SLNE) can be performed in tumescent local anesthesia (TLA) or general anesthesia (GA). Perioperative cortisol level changes and anxiety are common in surgical interventions and might be influenced by the type of anesthesia. In this study, we intended to determine whether the type of anesthesia impacts the patients’ perioperative levels of salivary cortisol (primary outcome) and the feeling of anxiety evaluated by psychological questionnaires (secondary outcome).